2014
DOI: 10.7863/ultra.33.3.503
|View full text |Cite
|
Sign up to set email alerts
|

Relative Proportions of Stromal to Cellular Components of Pleomorphic Adenomas

Abstract: Determination With Shear Wave Elastography easurement of tissue stiffness by sonography is a relatively new and expanding field of research. The principle theory in elastography is that malignant tumors are stiffer than benign ones. Preliminary evidence suggests that elastographic techniques may have a discriminatory value for detecting malignancies in the breast and thyroid gland. 1-3 However, elasticity imaging (both by qualitative and quantitative elastographic methods) is not definitive in distinguishing b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…This is caused by very variable histoarchitecture of salivary gland tumors which results in considerable variance in stiffness found both in our study ( Figure 3 ) and previously published papers [ 4 , 13 ]. Another complicating factor is the extremely wide range of elastographic values in pleomorphic adenomas (stiffness maxima may vary from 12.6 to 291.3 kPa) [ 6 ]. Due to its myxochondroid component, the stiffness of this benign lesion may be very high, overlapping that of malignant tumors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is caused by very variable histoarchitecture of salivary gland tumors which results in considerable variance in stiffness found both in our study ( Figure 3 ) and previously published papers [ 4 , 13 ]. Another complicating factor is the extremely wide range of elastographic values in pleomorphic adenomas (stiffness maxima may vary from 12.6 to 291.3 kPa) [ 6 ]. Due to its myxochondroid component, the stiffness of this benign lesion may be very high, overlapping that of malignant tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the statistical comparison between the two groups was not possible [ 13 ]. Olgun et al did not include any malignant tumor in their study at all [ 6 ]. In a group of 10 carcinomas, Wierzbicka et al reported the sensitivity of conventional ultrasound in differentiation of benign from malignant lesions to be 93.8% and 62.5%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, SWE effectively differentiated seminomas from nonseminomatous germ cell tumors. Recently, Olgun et al 13 used SWE to classify pleomorphic adenomas in terms of their stromal and cellular components. We thus sought to build on their work.…”
Section: Discussionmentioning
confidence: 99%
“…Precompression is a substantial factor in obtaining accurate results with elastography so that the operator should place the transducer onto the skin surface with light contact using ample coupling gel and keeping the transducer stationary during acquisitions in order to reduce compression on the structures[ 29 , 33 34 ]. SWE image was displayed along with the gray-scale ultrasound (US).…”
Section: Methodsmentioning
confidence: 99%